2005
DOI: 10.1063/1.1994951
|View full text |Cite
|
Sign up to set email alerts
|

Electrical detection of immobilized proteins with ungated AlGaN∕GaN high-electron-mobility Transistors

Abstract: Ungated AlGaN∕GaN high-electron-mobility transistor (HEMT) structures were functionalized in the gate region with aminopropyl silane. This serves as a binding layer to the AlGaN surface for attachment of fluorescent biological probes. Fluorescence microscopy shows that the chemical treatment creates sites for specific absorption of probes. Biotin was then added to the functionalized surface to bind with high affinity to streptavidin proteins. The HEMT drain-source current showed a clear decrease of 4μA as this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 22 publications
2
98
0
1
Order By: Relevance
“…Results, though contrary to classical assessment [13,[15][16][17][18], are congruent with recent HFET protein-sensing results [20,21,24,25,29,30,40]. Nonetheless, the notion that some immunoHFETs are feasible in physiological environments is not widely accepted, motivating direct demonstration of the proposition here.…”
Section: Resultsmentioning
confidence: 38%
“…Results, though contrary to classical assessment [13,[15][16][17][18], are congruent with recent HFET protein-sensing results [20,21,24,25,29,30,40]. Nonetheless, the notion that some immunoHFETs are feasible in physiological environments is not widely accepted, motivating direct demonstration of the proposition here.…”
Section: Resultsmentioning
confidence: 38%
“…Pioneering work has been carried out by Bermudez,10,11 who has analyzed the adsorption of different organic molecules, such as anilines or octanethiols on GaN surfaces, from the gas phase. In a recent publication Kang et al 12 have reported the electrical detection of immobilized proteins on AlGaN / GaN transistors, modified with aminopropyltriethoxysilane ͑APTES͒ molecules in a liquid phase reaction. However, the covalent immobilization of molecules was not proven.…”
mentioning
confidence: 99%
“…They are a Pd ring Schottky diode structure [34] and an open gate FET structure [41] and both are formed on a standard AlGaN/GaN HFET wafer so that future co-integration with signal processing HFETs is easily accomplished.…”
Section: Leakage Currents In Algan Schottky Diodesmentioning
confidence: 99%